TEACHERS’ PERSPECTIVES TOWARD SUCCESSFULNESS OF ENGLISH LANGUAGE TEACHING TO YOUNG LEARNERS - Siti Nurazizah; Maulidia Rachmawati Nur (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2018)
In response to the need of qualified teaching English in primary level, successful English teaching has become a crucial and challenging issue. This exploratory case study examines the perspectives of teachers regarding successful English language teaching for young learners. Data of this study was collected from multiple interviews with seven English teachers teaching in five Islamic Integrated Elementary Schools in Bogor that offer English as an additional language (EAL). The findings reveal that the participants of this study had relatively the same understanding or perspectives on teaching English for young learners on eight criteria among the nine criteria of successful English language teaching to young learners. It was also found that five criteria had 100% agreement and were in line with the theories of successful teaching English to young learners. There was one criterion that had 57% inlined result. There were three inlined criteria which were relatively the same amount with 86%. Therefore, the other criterion was not in accordance with the seven respondents with 0% agreement.